Pharmacologic treatment of fibromyalgia: an update - Li, Yang; Li, Yunshen; Wu, Shiya; Long, Meijuan; Chen, Xinyi; Wang, Yidan; Zhao, Jianan; He, Bingheng; Chang, Cen; Jiao, Juan (Frontiers in Pharmacology, 2025)
Fibromyalgia (FM) is a chronic pain disorder characterized by widespread musculoskeletal pain, frequently accompanied by fatigue, sleep disturbances, cognitive dysfunction, and mood disorders. Although the etiology is multifactorial, involving genetic, hormonal, immunological, and environmental contributors, the exact pathophysiological mechanisms remain unclear, and the heterogeneity of symptoms poses significant challenges for diagnosis and management. Diagnostic criteria have evolved over the years, with newer approaches reducing some limitations, yet sex-related differences in clinical presentation continue to challenge timely and accurate diagnosis. Pharmacological therapy remains unsatisfactory: only pregabalin, duloxetine, and milnacipran have gained U.S. FDA approval, providing clinically meaningful relief in a minority of patients, and their frequent adverse events limit adherence. Numerous other agents, including cyclobenzaprine, gabapentinoids, NMDA antagonists, cannabinoids, and sodium oxybate, have been evaluated, but most remain investigational or limited by safety concerns. Current guidelines emphasize that pharmacological interventions alone are insufficient and should be integrated with non-pharmacological strategies, especially patient education, exercise, and psychological support. This review summarizes the evidence on available and emerging pharmacological options for FM, highlights their limitations, and underscores the need for individualized, multimodal treatment strategies to improve patient outcomes and quality of life.